Integrated challenge test: a new approach evaluating quantitative risk assessment of Listeria in ready to eat foods - Paolo Matteini; Chiara Romani; Marco Romani; Stefano Colombo (Italian Journal of Food Safety, 2012)
The study was aimed to predict the maximum concentration of Listeria monocytogenes during the shelf life in chicken liver paté. The prediction has been performed using the integrated challenge test: a test based on the interaction between indigenous lactic flora and L. monocytogenes and their growth parameters. Two different approaches were investigated: the former is based on the time difference between the onset of the L. monocytogenes and the lactic flora stationary phases, while the latter is based on the lactic flora concentration capable to induct the stationary phase of L. monocytogenes. Three different strains of L. monocytogenes, isolated from meat products, were used to perform three challenge tests. Triplicate samples from three different batches of liver paté were inoculated with a single-strain inoculum of 1.8 Log CFU/g. Samples were then stored at 4°C, 8°C and 12°C. Lactobacillus spp. (ISO 15214:1998) and L. monocytogenes (UNI EN ISO 11290-02:2005) plate counts were performed daily on each sample until the stationary phase was reached by both populations. The challenge test results were input in the Combase software to determine the growth parameters, later used for the calculation method. Predictive data were then statically assessed against the results of two additional challenge tests using triplicate samples from two different batches, the same strains and the same single-strain inoculum. Samples from the first batch were stored for 5 days at 4°C + 5 days at 8°C + 5 days at 12°C; samples from the second batch were stored for 3 days at 4°C + 3 days at 8°C + 4 days at 12°C. The results obtained showed that both approaches provided results very close to the reality. Therefore the Integrated challenge test is useful to determine the maximum concentration of L. monocytogenes, by simply knowing the concentration of the concerned microbial populations at a given time.